Potensi Limbah Industri Marmer sebagai Media Pembelajaran Kimia Kontekstual berbasis Green Chemistry di SMAN 1 Campurdarat - Ariani, Dian; Pangestu, Divan Robi; Purwanto, Dwi; Amaliyah, Fitri; Suroso, Imam (Jurnal Simki Pedagogia, 2025)
This study aims to explore the potential of marble industry waste as a contextual chemistry learning medium that supports environmentally friendly learning practices in a high school located in a marble-producing area. The research uses a descriptive qualitative method to investigate how marble waste, particularly in the form of calcium carbonate powder, can be utilized in chemistry learning to minimize the use of hazardous chemicals and reduce laboratory waste. Data were collected through field observations at local marble industries, interviews with industry workers and chemistry teachers, and documentation of the marble processing stages and waste materials. The data were analyzed using a descriptive technique to interpret the findings based on real conditions in the field. The results show that marble waste has significant potential to be used in simple chemistry experiments such as acid-base reactions, identification of chemical compounds, and the study of geological processes. The use of locally sourced waste materials enhances students' understanding of chemistry concepts, increases learning motivation, and contributes to a safer and more sustainable school laboratory environment. The findings suggest that local industrial materials can be integrated effectively into science education to create meaningful and environmentally responsible learning experiences.